Economic effects of R&D supports - Hüseyin Emre Sayıcı; Mehmet Fatih Ulu (Koç University-TÜSIAD Economic Research Forum (ERF), 2023)
This study examines the economic effects of research and development (R&D) supports in the context of a program implemented in Türkiye between 2006-2019. Firms receiving the support differ positively from other firms in key economic indicators. Results indicate a 6% rise in patent registrations, 9% growth in value-added, 26% surge in total wages, 17% increase in per capita wages, 9% expansion in employment, 10% boost in productivity, 11% rise in exported product diversity, and 4% uptick in sales due to the support. Nonetheless, the effects on productivity and sales are statistically weaker than other impacts. The average impact of patents is also modest. Large-scale firms exhibit significant benefits, with a 33% rise in patent numbers and a 13% growth in sales. These firms effectively leverage support to commercialize R&D investments and innovations. Small-sized firms experience stronger productivity effects. Productivity gains grow with scale among SMEs, but large firms do not see positive productivity effects.
Keywords: O31; O32; O38; 330; R&D supports; TEYDEB; innovation; matching